Concussion assessment and management practices among irish and canadian athletic therapists: An international perspective - Lempke, L. B.; Bergeron, G.; O'Connor, S.; Lynall, R. C.; Resch, J. E.; Walton, S. R. (Journal of Athletic Training, 2023)
Context Certified athletic therapists in Ireland and Canada serve essential concussion assessment and management roles, but their health care practices and concussion knowledge have not been established.